2019
DOI: 10.1177/1528083719850832
|View full text |Cite
|
Sign up to set email alerts
|

One-step preparation of woven fabric-reinforced hydrogel composite

Abstract: Cotton-woven fabric-reinforced polyvinyl alcohol-based hydrogel composite was produced by constructing cotton as warp and polyvinyl alcohol/cotton hybrid and polyvinyl alcohol yarns as weft yarns in the fabric structure. As-prepared polyvinyl alcohol/cotton fabrics were treated with different concentrations of aqueous borax and glutaraldehyde crosslinking solutions. Polyvinyl alcohol molecules were transformed to crosslinked gel structure after the treatments. Since cotton yarns kept their yarn structure in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Due to the formation of more stable hydrogels within and between the yarns, inter and intra friction of yarns were developed and enhanced the mechanical performance of PVA/C with boraxwater treatment. Since the composites were tested in wet form, elongation at the break is higher in this study comparing with our previous study at warp direction [25]. Additionally, breaking strength increase with increasing borax concentration in the treatment solution at wet samples in this study, but breaking point decreased at dried composites except initial increase of borax concentration in the previous study [25].…”
Section: Mechanical Analysis Of Cotton Flax and Wool Fabric Reinforce...supporting
confidence: 41%
See 3 more Smart Citations
“…Due to the formation of more stable hydrogels within and between the yarns, inter and intra friction of yarns were developed and enhanced the mechanical performance of PVA/C with boraxwater treatment. Since the composites were tested in wet form, elongation at the break is higher in this study comparing with our previous study at warp direction [25]. Additionally, breaking strength increase with increasing borax concentration in the treatment solution at wet samples in this study, but breaking point decreased at dried composites except initial increase of borax concentration in the previous study [25].…”
Section: Mechanical Analysis Of Cotton Flax and Wool Fabric Reinforce...supporting
confidence: 41%
“…Since the composites were tested in wet form, elongation at the break is higher in this study comparing with our previous study at warp direction [25]. Additionally, breaking strength increase with increasing borax concentration in the treatment solution at wet samples in this study, but breaking point decreased at dried composites except initial increase of borax concentration in the previous study [25]. In another study, it was also confirmed that breaking strength gradually increased when the hydrogel composite released its water content [30].…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…The woven fabrics were treated with different concentrations of aqueous crosslinkers, namely borax and glutaraldehyde solutions. [ 142 ] In another study, woven cotton and viscose‐micromodal fabrics were loaded with caffeine nanoparticles for transdermal antioxidant patches. Once worn next to skin, the system can deliver caffeine for several hours without any further action from the patient.…”
Section: Classification Of Drug‐eluting Textilesmentioning
confidence: 99%